2015
DOI: 10.1080/19443994.2014.1003975
|View full text |Cite
|
Sign up to set email alerts
|

Isotherm and kinetic studies on the adsorption of nitrate onto nanoalumina and iron-modified pumice

Abstract: A B S T R A C TThe use of nanoalumina and iron-modified pumice (IMP) as adsorbents for removal of nitrate from aqueous solution was investigated. Adsorption experiments were carried out as a function of the pH, contact time, and concentration of nitrate. Both adsorbents were effective for the nitrate removal in a pH range of 4-6, and optimum removal of nitrate ions occurred in a pH 5.0. The adsorption of nitrate on both adsorbents reached equilibrium within 50 min. Nitrate sorption kinetics was well fitted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 42 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…There was no significant change in nitrate uptake by nanoalumina after 20 min. Similarly, Golestanifar et al 34 investigated the nitrate adsorption efficiency using nanoalumina and observed the maximum adsorption efficiency of 70.8 mg/g within the contatct time of 50 min. Natural zeolite and natural zeolite-supported zerovalent iron nanoparticles showed maximum nitrate adsorption efficiency of 1.4 and 8.9 mg/g at an equilibrium contact time of about 12 and 7 h, respectively.…”
Section: Effect Of Contact Time and Initial Concentration On No3adsormentioning
confidence: 99%
“…There was no significant change in nitrate uptake by nanoalumina after 20 min. Similarly, Golestanifar et al 34 investigated the nitrate adsorption efficiency using nanoalumina and observed the maximum adsorption efficiency of 70.8 mg/g within the contatct time of 50 min. Natural zeolite and natural zeolite-supported zerovalent iron nanoparticles showed maximum nitrate adsorption efficiency of 1.4 and 8.9 mg/g at an equilibrium contact time of about 12 and 7 h, respectively.…”
Section: Effect Of Contact Time and Initial Concentration On No3adsormentioning
confidence: 99%
“…The main substrate for feeding the SBR was included methanol, TBA and MTBE along with nutrients (nitrogen and phosphorus). Gas Chromatograph (Agilent model) was used for measuring the MTBE [6] , [7] , [8] . Low levels of essential elements (micro elements) were injected to SBR during application.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The extractives of cork include several organic compounds such as waxes, triterpenes, fatty acids, glycerides, phenols and polyphenols. The pH influences the chemical speciation and the diffusion rate of solutes, the dissociation of sorbent functional groups and the sorbent surface charge (Rahmani et al, 2010;Glestanifar et al, 2016). It is assumed that the PS affects the release of organic carbon, since it is directly related to surface area, although this effect might vary according to the initial wastewater pH.…”
Section: Effect Of Ps and Ph On The Release Of Organic Carbonmentioning
confidence: 99%